Experiencias de madres con el uso de fórmulas lácteas y sus implicaciones en salud oral (2023)
Introduction: According to the experiences with the mothers, a critical analysis of the implications on oral health due to the use of milk formulas was carried out, from the phenomenological investigation a vision on the state of the subject is developed.